Evaluation of different control methods against citrus rind borer (Prays endolemma Diakonoff) - Aceres, Larry V.; Mamangun, Marjun A.; Pelicano, Emelie G.; Esteban, Jerald Anthony P.; Paulite, Jesryl L. (2019)
The Citrus rind borer also known as citrus pock caterpillar is still the most critical pest-infesting pummelo (Citrus maxima Merr.) in the Philippines particularly in Davao region. Management of the pest is indispensable for successful pummelo production. The study was conducted to determine the best cost-effective treatment to manage the pest-infesting pummelo. The experiment was laid out in Completely Randomized Design (CRD) with five treatments replicated three times. The treatment were: curry tree leaf leachate, neem tree leaf leachate , bagging with an ordinary net, treated check (Chlorpyrifos + Beta-cyfluthrin), and untreated check. Data were analyzed using Analysis of Variance while the differences among treatment means were computed using the Tukey's Honest Significant Difference. Results revealed that the cost-effective treatment against the destructive citrus rind borer is the bagging treatment. Bagging of fruits is more economical and environmentally sound over the use of chemical pesticides (Chlorpyrifos + Beta-cyfluthrin).
Keywords: Pummelo; Fruit diseases and pests; Mindanao studies